Microbiomes Associated With the Surfaces of Northern Argentinian Fruits Show a Wide Species Diversity - Vermote, Louise; Verce, Marko; Mozzi, Fernanda; De Vuyst, Luc; Weckx, Stefan (Frontiers in Microbiology, 2022)
The fiber, vitamin, and antioxidant contents of fruits contribute to a balanced human diet. In countries such as Argentina, several tropical fruits are witnessing a high yield in the harvest season, with a resulting surplus. Fruit fermentation using autochthonous starter cultures can provide a solution for food waste. However, limited knowledge exists about the microbiota present on the surfaces of fruits and the preceding flowers. In the present exploratory study, the microbiomes associated with the surfaces of tropical fruits from Northern Argentina, such as white guava, passion fruit and papaya were investigated using a shotgun metagenomic sequencing approach. Hereto, one sample composed of 14 white guava fruits, two samples of passion fruits with each two to three fruits representing the almost ripe and ripe stage of maturity, four samples of papaya with each two to three fruits representing the unripe, almost ripe, and ripe stage of maturity were processed, as well as a sample of closed and a sample of open Japanese medlar flowers. A considerable heterogeneity was found in the composition of the fruits’ surface microbiota at the genus and species level. While bacteria dominated the microbiota of the fruits and flowers, a small number of the metagenomic sequence reads corresponded with yeasts and filamentous fungi. A minimal abundance of bacterial species critical in lactic acid and acetic acid fermentations was found. A considerable fraction of the metagenomic sequence reads from the fruits’ surface microbiomes remained unidentified, which suggested that intrinsic species are to be sequenced or discovered.